Effect of Home-Based High-Intensity Interval Training in Patients With Lacunar Stroke: A Randomized Controlled Trial - Steen Krawcyk, Rikke; Vinther, Anders; Petersen, Nicolas Caesar; Faber, Jens; Iversen, Helle K.; Christensen, Thomas; Lambertsen, Kate Lykke; Rehman, Shazia; Klausen, Tobias Wirenfeldt; Rostrup, Egill; Kruuse, Christina (Frontiers in Neurology, 2019)
Background High-intensity interval training (HIIT) is superior to moderate-intensity continuous training in improving cardiorespiratory fitness in patients with cardiovascular disease, but is it safe, feasible and effective in patients with stroke. The aim was to investigate feasibility and effect of early home-based HIIT in patients with lacunar stroke combined with usual care versus usual care, only. Methods In a 1:1 ratio patients were randomized to HIIT or usual care in a randomised controlled trial. We measured the following outcomes at baseline and post-intervention: cardiorespiratory fitness monitored as power output from the Graded Cycling Test with Talk Test (GCT-TT; primary outcome), physical activity, fatigue, depression, well-being, stress, cognition, endothelial function, blood pressure, body mass index, and biomarkers. The study was registered at: (URL: https://clinicaltrials.gov, ID: NCT02731235) Results We included 71 patients (mean age 63.7±9.2) 49 men, 31 in intervention group. Home-based HIIT was feasible with no reported adverse events. Changed power output in GCT-TT was 8W and 9W, intervention and usual care group, respectively (p=0.91). The change in time spent on vigorous-intensity activity was 2 hours/week and 0.6 hours/week, intervention and usual care respectively (p=0.045). There were no significant differences between groups in the remaining secondary outcomes. Conclusion HIIT was feasible and safe in patients with lacunar stroke. Patients can engage early in home-based HIIT when involved in choosing exercise modality and guided by weekly motivational phone calls. Within three months, HIIT did however not yield corresponding effect on cardiorespiratory fitness. We await further evaluation of long-term effect of this intervention on continued regular physica exercise and cardiovascular event. Keywords: aerobic exercise, high-intensity interval training, home-based physical activity, secondary stroke prevention, lacunar stroke